10
$\begingroup$

Variation of my recent post. Strangely it leads to the result in term of Euler's constant;$\gamma$

Prove that

$$\int_{0}^{1}\int_{0}^{1}\left({x\over 1-xy}\cdot{\ln{x}-\ln{y}\over \ln{x}+\ln{y}}\right)\mathrm dx\mathrm dy=1-2\gamma$$

Where $\gamma=0.577215...$;Euler's constant.

My try:

$u=xy$ then $du=ydx$

$$\int_{0}^{1}\int_{0}^{y}{{u\over y^2}\over 1-u}\cdot{\ln{u\over y^2}\over \ln{u}}\mathrm du\mathrm dy$$

I can't understand how to or even glimsely to solve double integrals.

Any chance can someone show me a detail of the answer. Thank you.

$\endgroup$
  • $\begingroup$ the proposed approach in the other question doesn't work? $\endgroup$ – tired Jan 3 '17 at 11:19
  • 1
    $\begingroup$ Changing the order of integration we get $$ \int_0^1du\frac{u}{1-u}\int_u^1dv\frac{1}{v^2}\left(1-2\frac{\log(v)}{\log(u)}\right) $$ the inner integral is straightforward and you only need integral representation 5 from here en.wikipedia.org/wiki/… $\endgroup$ – tired Jan 3 '17 at 11:27
  • $\begingroup$ For a proof of different integral reps of Euler's constant see here: math.stackexchange.com/questions/980593/… $\endgroup$ – tired Jan 3 '17 at 11:41
10
+50
$\begingroup$

Folllowing @tired Comment(s): $$ \begin{align} \text{Let} &\colon\space x\,y=u,\,\,y=v \space\Rightarrow\space x/y=u/v^2,\,\,y\,dx=du,\,\,dy=dv \\[3mm] \color{red}{I} &= \int_{0}^{1}\int_{0}^{1}\left(\frac{x}{1-x\,y}\,\frac{\log{x}-\log{y}}{\log{x}+\log{y}}\right)\,dx\,dy = \int_{0}^{1}\int_{0}^{1}\left(\frac{(x/y)}{1-(x\,y)}\,\frac{\log{(x/y)}}{\log{(x\,y)}}\right)\,(y\,dx)\,dy \\[3mm] &= \int_{0}^{1}\int_{0}^{v}\left(\frac{(u/v^2)}{1-u}\,\frac{\log{(u/v^2)}}{\log{u}}\right)\,du\,dv = \int_{0}^{1}\int_{\color{red}{0}}^{\color{red}{v}}\left[\frac{u}{1-u}\,\frac{1}{v^2}\left(1-2\frac{\log{v}}{\log{u}}\right)\right]\color{red}{\,du\,dv} \\[3mm] &= \int_{0}^{1}\int_{\color{red}{u}}^{\color{red}{1}}\left[\frac{u}{1-u}\,\frac{1}{v^2}\left(1-2\frac{\log{v}}{\log{u}}\right)\right]\color{red}{\,dv\,du} \quad\qquad\qquad\qquad\qquad\qquad\color{blue}{\{1\}} \\[3mm] &= \int_{0}^{1}\frac{u}{1-u}\,du\,\int_{u}^{1}\left(\frac{1}{v^2}-\frac{2}{\log{u}}\frac{\log{v}}{v^2}\right)\,dv \\[3mm] &= \int_{0}^{1}\frac{u}{1-u}\,du\,\left[-\frac{1}{v}+\frac{2}{\log{u}}\frac{1+\log{v}}{v}\right]_{u}^{1} \qquad\qquad\qquad\qquad\qquad\qquad\color{blue}{\{2\}} \\[3mm] &= \int_{0}^{1}\frac{u}{1-u}\left(\frac{-2}{\log{u}}\frac{1-u}{u}-\frac{1+u}{u}\right)\,du = \int_{0}^{1}\left(\frac{-2}{\log{u}}-\frac{1+u}{1-u}\right)\,du \\[3mm] &= \int_{0}^{1}\left(\frac{-2}{\log{u}}-\frac{1+u\color{red}{-1+1}}{1-u}\right)\,du = \int_{0}^{1}\left(\frac{-2}{\log{u}}+\frac{-2}{1-u}+1\right)\,du \\[3mm] &= \int_{0}^{1}\,du\,-2\int_{0}^{1}\left(\frac{1}{\log{u}}+\frac{1}{1-u}\right)\,du = \color{red}{1 - 2\,\gamma} \quad\qquad\qquad\qquad\qquad\color{blue}{\{3\}} \\[3mm] \end{align} $$

$\,\color{blue}{\{1\}}\colon\,$ Change order integration.
$\,\color{blue}{\{2\}}\colon\,$ IBP: $\,\int\log{x}\,\frac{dx}{x^2},\,\{u=\log{x}\,{\small\Rightarrow}\,du=\frac{dx}{x},\, dv=\frac{dx}{x^2}\,{\small\Rightarrow}\,v=\frac{-1}{x}\},\,=-\frac{\log{x}}{x}+\int\frac{dx}{x^2}=-\frac{1+\log{x}}{x}$.
$\,\color{blue}{\{3\}}\colon\,$ Integral Representation of Euler–Mascheroni Constant: $\quad\gamma = \int_{0}^{1}\left(\frac{1}{\log{x}}+\frac{1}{1-x}\right)\,dx$.

$\endgroup$
  • $\begingroup$ @Algebra: Thanks. $\endgroup$ – Hazem Orabi Jan 21 '17 at 8:31
  • $\begingroup$ No, thanks you for answering the question @Hazem Orabi $\endgroup$ – gymbvghjkgkjkhgfkl Jan 21 '17 at 17:55
4
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[8px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$

$\ds{\int_{0}^{1}\int_{0}^{1}{x \over 1 - xy}\, {\ln\pars{x} - \ln\pars{y} \over \ln\pars{x} + \ln\pars{y}}\,\dd x\,\dd y = 1 - 2\gamma\,,\qquad\gamma:\ Euler\mbox{-}Mascheroni\ Constant}$.

\begin{align} &\int_{0}^{1}\int_{0}^{1}{x \over 1 - xy}\, {\ln\pars{x} - \ln\pars{y} \over \ln\pars{x} + \ln\pars{y}}\,\dd x\,\dd y \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{1}\int_{0}^{1}{x \over 1 - xy} \pars{x^{\mu} - y^{\mu}} \bracks{-\int_{0}^{\infty}\pars{xy}^{\,t}\,\dd t}\,\dd x\,\dd y\, \right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1}\int_{0}^{1} {x^{t + 1}y^{t + \mu} - x^{t + \mu + 1}y^{t} \over 1 - xy} \,\dd x\,\dd y\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1}\int_{0}^{y} {x^{t + 1}y^{\mu - 2} - x^{t + \mu + 1}y^{-\mu - 2} \over 1 - x} \,\dd x\,\dd y\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1}\int_{x}^{1} {x^{t + 1}y^{\mu - 2} - x^{t + \mu + 1}y^{-\mu - 2} \over 1 - x} \,\dd y\,\dd x\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1} \pars{x^{t + 1}\,{1 - x^{\mu - 1} \over \mu - 1} + x^{t + \mu + 1}\,{1 - x^{-\mu - 1}\over \mu + 1}} {\dd x\,\dd t \over 1 - x}\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty}\int_{0}^{1} \pars{{1 \over \mu - 1}\,{x^{t + 1} - x^{t + \mu} \over 1 - x} + {1 \over \mu + 1}\,{x^{t + \mu + 1} - x^{t} \over 1 - x}} \dd x\,\dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\int_{0}^{\infty} \bracks{{\Psi\pars{t + \mu + 1} - \Psi\pars{t + 2} \over \mu - 1} + {\Psi\pars{t + 1} - \Psi\pars{t + \mu + 2} \over \mu + 1}} \dd t\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \left.\partiald{}{\mu}\bracks{% {1 \over \mu - 1}\,\ln\pars{\Gamma\pars{t + \mu + 1} \over \Gamma\pars{t + 2}} + {1 \over \mu + 1}\,\ln\pars{\Gamma\pars{t + 1} \over \Gamma\pars{t + \mu + 2}}} _{\ t\ =\ 0}^{\ t\ \to\ \infty}\, \right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \partiald{}{\mu}\bracks{% -\,{\ln\pars{\Gamma\pars{\mu + 1}} \over \mu - 1} + {\ln\pars{\Gamma\pars{\mu + 2}} \over \mu + 1}}_{\ \mu\ =\ 0} = \Psi\pars{1} + \Psi\pars{2} = 2\Psi\pars{1} + 1 = \bbx{\ds{1 - 2\gamma}} \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.